Jump for joy (Astra Young Readers, an imprint Astra Books for Young Readers, 2024)
Kid seeks dog. Dog seeks kid. In this charming and imaginative tale of friendship, picture book readers will delight in what it means to have a furry best friend. For as long as she can remember, Joy has wanted a dog. It doesn’t matter what kind: big, little, spotted, curly. She wants one so fiercely, she makes dogs out of snow, seashells, or whatever’s at hand! However, none of the dogs Joy makes are quite what she yearns for. The seashell dog washes away, and the snow dog melts into a puddle. Little does Joy know that her perfect dog friend is just around the corner—wishing just as fiercely for a kid—and waiting to be discovered. Award-winning artist Hadley Hooper creates a world that is both timeless and magical as she weaves ink, paint, and collages made from vintage etchings together in a style that perfectly complements the classic feel of Jump for Joy. Readers will rejoice in this satisfying kid-meets-dog story, and will savor returning to this world again and again.